Ontological Investigations. An Inquiry into the Categories of Nature, Man and Society - Johansson, Ingvar (Reprint Philosophy, 2004)
This volume is devoted to problems within analytic metaphysics. It defends an ontology and theory of categories inspired by Aristotle, but revised in such a way as to be compatible with modern science. The ontology of both natural and social reality is addressed, starting out from the view that universals exist but only in the spatiotemporal world (immanent realism). In attempting to bring Aristotle's ontology up-to-date, the author relies very much on the thinking of Edmund Husserl, conceiving the cement of the universe as Husserlian relations of existential dependence and regarding intentionality as a non-reducible category in the ontology of mind. The work is thoroughly realistic in spirit, but large parts of it should nonetheless be of interest to conceptualists and nominalists, too.